2014
DOI: 10.1039/c3fo60050e
|View full text |Cite
|
Sign up to set email alerts
|

A fucose containing polymer-rich fraction from the brown alga Ascophyllum nodosum mediates lifespan increase and thermal-tolerance in Caenorhabditis elegans, by differential effects on gene and protein expression

Abstract: The extracts of the brown alga, Ascophyllum nodosum, which contains several bioactive compounds, have been shown to impart biotic and abiotic stress tolerance properties when consumed by animals. However, the physiological, biochemical and molecular mechanism underlying such effects remain elusive. We investigated the effect of A. nodosum fucose-containing polymer (FCP) on tolerance to thermally induced stress using the invertebrate animal model, Caenorhabditis elegans. FCP at a concentration of 150 μg mL(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…L-Fucose is a constituent of many structural polysaccharides and glycoproteins in various organisms and plays important metabolic roles in complex carbohydrates and glycoproteins. It can also induce antioxidant activity against oxidative stress (Kandasamy et al, 2014;Vermeer et al, 2001). The accumulation of GDP-L-fucose at 45°C and 52°C indicated that the antioxidant protection of E. malaccana may change as thermal stress intensifies; reliance on dipeptides is reduced and other systems like those induced by GDP-L-fucose assume greater importance.…”
Section: Regulation Of the Cellular Stress Responsementioning
confidence: 99%
“…L-Fucose is a constituent of many structural polysaccharides and glycoproteins in various organisms and plays important metabolic roles in complex carbohydrates and glycoproteins. It can also induce antioxidant activity against oxidative stress (Kandasamy et al, 2014;Vermeer et al, 2001). The accumulation of GDP-L-fucose at 45°C and 52°C indicated that the antioxidant protection of E. malaccana may change as thermal stress intensifies; reliance on dipeptides is reduced and other systems like those induced by GDP-L-fucose assume greater importance.…”
Section: Regulation Of the Cellular Stress Responsementioning
confidence: 99%
“…After heat stress, Kandasamy et al (2014) also observed higher survival of the worm Caenorhabditis elegans fed a commercial product derived from the brown seaweed Ascophyllum nodosum . The authors stated that this increased survival was associated with an improvement of antioxidant activity, as well as changes in major stress‐related proteins and gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…After heat stress, Kandasamy et al (2014) followed by lipid peroxidation and DNA damage. All these mechanisms can trigger the ER stress and apoptosis machinery, resulting in serious physiological damage to the organism (Hayward et al, 2014;Hermes-Lima et al, 2015;Qiu et al, 2011;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation